Procedural trends, outcomes, and readmission rates pre‐and post‐FDA approval for MitraClip from the National Readmission Database (2013–14). Issue 6 (20th November 2017) - Panaich, Sidakpal S.; Arora, Shilpkumar; Badheka, Apurva; Kumar, Varun; Maor, Elad; Raphael, Claire; Deshmukh, Abhishek; Reeder, Guy; Eleid, Mackram; Rihal, Charanjit S.
Abstract: Background: There are sparse clinical data on the procedural trends, outcomes and readmission rates following FDA approval and expansion of Transcatheter mitral valve repair/MitraClip ® . Whether a complex new technology can be disseminated safely and quickly is controversial. Methods: The study cohort was derived from the National Readmission Data (NRD) 2013–14. MitraClip ® was identified using appropriate International Classification of Diseases, 9th Revision, Clinical Modification (ICD‐9‐CM) codes. The primary outcome was a composite of in‐hospital mortality + procedural complications. Secondary outcome included 30‐day readmissions. Hierarchical two level logistic models were used to evaluate study outcomes. Results: Our analysis included 2003 MitraClip ® procedures. Overall in‐hospital mortality was 3.9%. As expected, there was a significant increase in procedural volume post‐FDA approval. Importantly, a corresponding downward trend in mortality and procedural complications was observed. Significant predictors of in‐hospital mortality and procedural complications included the use of vasopressors ( P <0.001) and hemodynamic support ( P < 0.001). Higher hospital volume (≥10 MitraClips/year) was associated with lower in‐hospital mortality and complications ( P = 0.02). There were 304 (15.1%) 30‐day readmissions, with heart failure being the most common cause of readmission. Elective procedures had lower in‐hospital mortality ( P < 0.001) and lower readmission rates ( P = 0.011) compared with nonelective procedures. Conclusion: A significant increase in MitraClip ® procedural volumes occurred post‐FDA approval. Overall morbidity and mortality were low and trended downwards. Hospital procedure volume ≥10 cases were associated with lower mortality and overall complication rates. These data suggest a successful roll out of a very complex novel structural heart procedure.